2020
DOI: 10.1007/s40744-020-00226-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility and Cost Savings in Predicting Inadequate Response to Anti-TNF Therapies in Rheumatoid Arthritis

Abstract: Introduction: The PrismRA Ò test identifies rheumatoid arthritis (RA) patients who are unlikely to respond to anti-tumor necrosis factor (anti-TNF) therapies. This study evaluated the clinical and financial outcomes of Digital Features To view digital features for this article go to:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“… 3 This lack of efficacy has many negative downstream consequences, including disease progression, increased disease risks by unnecessary immunomodulatory therapies, and a significant waste of economic resources. 4 Understanding the source of this heterogeneity not only will help to direct patients to the most efficacious therapy, but also could provide insights into new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“… 3 This lack of efficacy has many negative downstream consequences, including disease progression, increased disease risks by unnecessary immunomodulatory therapies, and a significant waste of economic resources. 4 Understanding the source of this heterogeneity not only will help to direct patients to the most efficacious therapy, but also could provide insights into new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Since the demand for specific tests aiding therapy decisions is high, different efforts regarding biologic therapy prediction have been made. Most of them though focus on a genomic or proteomic attempt, e.g., [ 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strategic approaches need to be in place like changing regulations governing health insurance as well as pharmaceutical companies to overcome the cost challenges involved in bringing PM to deliver improved health outcomes to a broader sector of patients. A recent study showed that stratifying patients according to PM-based approaches could save approximately $7 million in overall healthcare costs per 1,000 patients ( 237 ). In that context, detection of HER2, a validated biomarker in a specific cohort of patients with breast cancer overexpressing HER2 in tumors, reduced the clinical trial risk by 50 and 27% reduction in cost ( 238 ).…”
Section: The Downside Of Pmmentioning
confidence: 99%